Facteurs Lies Au Stress Chez Les Couples Infertiles A Partir De Cas Recenses A L’unite Biologique De La Reproduction De L’institut Pasteur d’Abidjan - Koffi Samson; Coulibaly Founzégué Amadou; Kouame Atta; Kone Drissa (European Scientific Journal, ESJ, 2018)
The stress associated with infertility is a painful experience for couples who are struggling to conceive of the value attached to the child in African society. This article apprehends the question of the management of stress caused by infertility from the cases identified at “Institut pasteur d’Abidjan”. The methodology adopted concerns observation techniques, semi-structured interview as well as the use of stress scale submitted to a sample of 120 subjects, including 60 men and 60 infertile women. The data collected were processed manually with proportion calculations. The results indicate that the majority of clients (73.33%) experience episodes of stress related to their infertility whose main sources are biological, psychological and environmental. In sum, the existence of a holistic support network can effectively communicate infertility and reduce the effect of these factors.